Place - Dean, Tacita 1965-; Millar, Jeremy (New York, N.Y. Thames & Hudson, 2005)
"This exhibition in a book presents some of the most challenging art to address the function of place in the contemporary world. Arranged into themed "rooms", it reflects a wide variety of artistic attitudes and practices. Some artists find inspiration in the heterogeneity of the crowded city street, while others celebrate the wilds of nature. Some present imagined or fantastic worlds, exploring the way place is often a creation of the mind. Others investigate the deep marks that myth and history can leave on the land, or consider how place can be used as a form of political control. Territorial divisions demarcating one place from another, often with terrible consequences, are the chosen subject-matter of many artists; others prefer to look at itinerant wanderers with no claims on the earth." -- Provided by publisher
Includes bibliographical references (page 204) and index.
Keywords: Place (Philosophy) in art; Art, Modern -- 20th century; Art, Modern -- 21st century